Molecular Identification of Several Morphologically Distinct Flowerhorn Fish (Family) Using Mitochondrial COI Gene Marker - Dini Wahyu Kartika Sari; Himawan Achmad; Hafit Rahman; Harya Bimasuci (Universitas Gadjah Mada, 2023)
Flowerhorn fish has been known as a breed of fish produced by artificial hybridization between several cichlid fish. Other ornamental cichlid fish generally known to be crossed to make flowerhorn variant includes Amphilophus citrinelus, Amphilophus labiatus, Vieja melanurus, and Amphilophus trimaculatus. Our study identified a variety of flowerhorn samples with distinct morphotypes, dubbed as Cencu (LH1CC), Kamfa (LH2KF), Thai Silk (LH3TS), Kirin (LH4KR), Parrot (LH5PR), and Vieja (LH6VJ) using mtDNA COI-based DNA barcoding. Molecular analysis and phylogenetics showed that all sample had 0% genetic divergence and conspecific with A. trimaculatus sequence. Hence, we concluded that despite having varied morphotypes, all flowerhorn samples were identified as A. trimaculatus and were a variation of flowerhorn from A. trimaculatus lineage. The findings should be used as a precaution as the fish is identified as an invasive species.